Cognitive assessment of children at age 2½ years after maternal fish oil supplementation in pregnancy: a randomised controlled trial. Issue 1 (21st December 2006) - Dunstan, J A; Simmer, K; Dixon, G; Prescott, S L
Abstract : Objective: To assess the effects of antenatal omega 3 long-chain polyunsaturated fatty acid (n-3 LC PUFA) on cognitive development in a cohort of children whose mothers received high-dose fish oil in pregnancy. Design: A double-blind randomised placebo-controlled trial. Setting: Perth, Western Australia, Australia. Patients: 98 pregnant women received the supplementation from 20 weeks' gestation until delivery. Their infants (n = 72) were assessed at age 2½ years. Interventions: Fish oil (2.2 g docosahexaenoic acid (DHA) and 1.1 g eicosapentaenoic acid (EPA)/day) or olive oil from 20 weeks' gestation until delivery. Outcome measures: Effects on infant growth and developmental quotients (Griffiths Mental Development Scales), receptive language (Peabody Picture Vocabulary Test) and behaviour (Child Behaviour Checklist). Results: Children in the fish oil-supplemented group (n = 33) attained a significantly higher score for eye and hand coordination (mean ((SD) score 114 (10.2)) than those in the placebo group (n = 39, mean score 108 (SD 11.3); p = 0.021, adjusted p = 0.008). Eye and hand coordination scores correlated with n-3 PUFA levels in cord blood erythrocytes (EPA: r = 0.320, p = 0.007; DHA: r = 0.308, p = 0.009) and inversely correlated with n-6 PUFA (arachidonic acid 20:4n-6: r = −0.331, p = 0.005). Growth measurements in the two groups were similar at age 2½ years. Conclusion: Maternal fish oil supplementation during pregnancy is safe for the fetus and infant, and may have potentially beneficial effects on the child's eye and hand coordination. Further studies are needed to determine the significance of this finding.